2016
DOI: 10.1016/j.heliyon.2016.e00155
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon from flash pyrolysis of eucalyptus residue

Abstract: Forestry waste (eucalyptus sp) was converted into activated carbon by initial flash pyrolysis followed carbonization and CO2 activation. These residues were obtained from a pilot plant in Spain that produces biofuel, the biochar represented 10–15% in weight. It was observed that the highest activation was achieved at a temperature of 800 °C, the specific surface increased with time but, on the contrary, high loss of matter was observed. At 600 °C, although there was an important increase of the specific surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Similar findings were reported by Grima-Olmedo et al [124], Guo and Lua [120], Işıtan et al [125], Jung and Kim [126], and Sricharoenchaikul et al [127]. The adsorption-desorption curves showed a hysteresis loop, indicating increased mesopore volume, contrary to low temperature (873 K) activation, which obtained predominantly microporosity.…”
Section: Physical or Thermal Activationsupporting
confidence: 86%
“…Similar findings were reported by Grima-Olmedo et al [124], Guo and Lua [120], Işıtan et al [125], Jung and Kim [126], and Sricharoenchaikul et al [127]. The adsorption-desorption curves showed a hysteresis loop, indicating increased mesopore volume, contrary to low temperature (873 K) activation, which obtained predominantly microporosity.…”
Section: Physical or Thermal Activationsupporting
confidence: 86%
“…Upscaling the production of activated biochars may reduce the efficiency of heating and mass transfer in the char bed, lowering the porosity of materials compared to other wood waste activated biochars available in the literature (SBET higher than 1000 m 2 g -1 ) [27,42,46]. These high surface areas were reached through laboratory furnaces where the conditions of temperature and flow gases were well controlled while N2 and CO2 were efficiently in contact with the low amount of material placed in the furnace in a static position.…”
Section: Influence Of Pyro-gasification and Activation Conditions On The Porosity Of Activated Biochars And Practical Implicationsmentioning
confidence: 99%
“…Abundant literature have examined the influence of activation parameters (e.g., activation temperature, activation time, gas flow rate, impregnation chemical, biochar ratio) on porosity development in activated biochars [24]. The results show that processing conditions at high activation temperature (e.g., 900 °C) [25][26][27][28][29][30][31], high CO2 or steam flow rate [32,33], longer residence time (e.g., 2h) [25,26,32,[34][35][36][37], and high chemical impregnation ratio [38][39][40] produce highly porous materials. However, little attention has been paid to the different pyro-gasification (i.e., an integrative term that comprises all thermochemical processes such as torrefaction, slow to fast pyrolysis, and gasification) conditions for biochar production or how these conditions affect the porosity of activated biochars.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to bio-oil, flash pyrolysis can be used to produce activated carbon, as studied by (GRIMA-OLMEDO et al, 2016), who evaluated the recovery of forest residues of Eucalyptus sp. It was observed that the activation of the charcoal surface depends on the temperature at which the thermochemical conversion process is conducted.…”
Section: Flash Pyrolysismentioning
confidence: 99%
“…Both the yield and the chemical composition of the products obtained by means of flash pyrolysis are significantly influenced by the pyrolysis parameters (temperature and heating rate), production system (reactor) and the characteristics of the biomass used as a feedstock (AARUM et al, 2017;GRIMA-OLMEDO et al, 2016).…”
Section: Flash Pyrolysismentioning
confidence: 99%